Comparison of live‐trapping and noninvasive genetic sampling to assess patch occupancy by New England cottontail (Sylvilagus transitionalis) rabbits. (9th September 2013) - Kilpatrick, Howard J.; Goodie, Travis J.; Kovach, Adrienne I.
ABSTRACT The New England cottontail (Sylvilagus transitionalis) is a species of high conservation priority in the northeastern United States and a candidate for federal listing under the Endangered Species Act. Eastern cottontails are abundantly distributed and similar in appearance to New England cottontails. Our objective was to compare cost, effort, and effectiveness of live‐trapping and noninvasive genetic monitoring for assessing patch occupancy by New England cottontail. We collected 113 tissue samples and 240 fecal pellets samples for diagnostic genetic testing to detect species presence and assess the proportion of samples consisted of New England and eastern cottontail on 5 study sites in Connecticut in 2008 and 2009. Both methods detected presence of New England cottontail at 4 of 5 sites. Overall proportion of DNA samples consisted of New England cottontail was similar between sampling methods (χ2 = 0.189, P = 0.664). However, species composition on individual sites was inconsistent between methods and no clear pattern of bias was discernible. Mean cost per DNA sample to collect and analyze was US433 for tissue samples and US33 for fecal pellets. Samples collected per person‐day of effort were 40 for fecal samples and 0.7 for tissue samples. Genetic monitoring via noninvasive fecal sampling was a low‐cost, time‐efficient method for assessing species occupancy, but development of an optimal sampling strategy is needed to evaluate composition and distributions of species on sympatrically occupied sites. © 2013 The Wildlife Society.